Pengaruh lama thawing dengan air dingin pada semen beku Sapi Peranakan Ongole terhadap kualitas semen - Nursahida Ramadhani; Achadiah Rachmawati; Ahmad Budi Purnawan; Trinil Susilawati; Aulia Puspita Anugra Yekti (Universitas Sebelas Maret, 2022)
Objective: The purpose of this research was to determine the effect of thawing durations using cold water on Ongole Crossbred Bull frozen semen towards semen quality including motility, viability, abnormality and total motile spermatozoa.Methods: The method used was experimental in the laboratory using five treatments and ten replications on frozen semen samples of Ongole Crossbred Bull. The data were analyzed using Randomized Block Design variance and continued with DMRT if there was a significant difference. Motility and total motile spermatozoa were tested by Chi Square test to compare with the SNI standard for frozen semen quality. In this research, five treatments were carried out, T0 with a thawing time of 30 seconds with a temperature of 37 oC, while T1, T2, T3 and T4 each used a thawing time of 15, 30, 45 and 60 seconds with temperature of 28 oC.Results: The best thawing results were T2 with individual motility 49.9 ± 6.0 %, viability 65.1 ± 7.2 %, abnormality 4.0 ± 1.8 %, concentration of 39.1 ± 10.2 million/straw and total motile spermatozoa 19.3 ± 4.0 million/straw.Conclusions: In conclusion, the duration and temperature of thawing can affected the quality of Ongole Crossbred frozen semen.